High-frequency characteristics of InGaP/GaAs double heterojunction bipolar transistor epitaxially grown on 200 mm Ge/Si wafers - Loke, Wan Khai (2020)
N-p-n InGaP/GaAs double heterojunction bipolar transistor has been successfully grown on a 200 mm Ge/Si wafer using metalorganic chemical vapor deposition with low defect density of 107 cm ^{-2}. Non-gold metals of Ni/Ge/Al and Ti/Al are used to form the ohmic contact for small pieces device fabrication. Both direct-current (dc) and high-frequency characteristics of the device were measured. The device with emitter area of 6×8 μ {\text {m}} shows a dc gain of 55 at a collector current of I-{c} = 4 mA, with high collector-emitter breakdown voltage of 17 V. The high-frequency response with cutoff frequency ( f_{T} T) of 23 GHz and maximum available frequency ( f_{\text {max}} T) of 10 GHz can be achieved. These results demonstrate that InGaP/GaAs double heterojunction bipolar transistor grown on low defect density Ge/Si wafer has the potential for realizing III-V CMOS integrated platform for high-frequency applications.